Erratum to “Improvement of growth and yield of soybean plants through the application of non-thermal plasmas to seeds with different health status” [Heliyon Volume 5, Issue 4, April 2019, e01495] - Pérez Pizá, María Cecilia (2020)
In the original published version of this article, some authors wereomitted from certain references. The corrected references are shownbelow. This error was introduced during the typesetting of the article, thepublisher apologises for this error. Both the HTML and PDF versions ofthe article have been updated to correct the error.